Komunikasi Interpersonal dalam Pembelajaran Digital: Studi Kasus Live TikTok @broaal.english - Ismail Muslimin; Zulaikha; Didik Sugeng Widiarto (Jurnal Komunikasi Profesional, 2026)
This study analyzes interpersonal communication in digital learning via TikTok live streaming on the account @broaal.english, focusing on social presence and audience engagement. Using a qualitative case study method, data was collected from eight live sessions and included audience interactions and statistical engagement metrics. Findings revealed that the host, referred to as "Uncle," fostered effective communication through relatable language, humor, and expressive nonverbal cues. The interactive Q&A sessions showcased strong audience involvement, leading to Uncle being perceived as a supportive figure. Statistical data indicated robust engagement with 50,000 followers and high viewership. The study concludes that effective interpersonal communication and social presence transform TikTok live sessions into interactive digital classrooms, contributing to understanding communication in social media-based learning.